Horizontal Bilayer for Electrical and Optical Recordings - Bartsch, Philipp (Materials (Basel), 2012)
Artificial bilayer containing reconstituted ion channels, transporters and pumps serve as a well-defined model system for electrophysiological investigations of membrane protein structure–function relationship. Appropriately constructed microchips containing horizontally oriented bilayers with easy solution access to both sides provide, in addition, the possibility to investigate these model bilayer membranes and the membrane proteins therein with high resolution fluorescence techniques up to the single-molecule level. Here, we describe a bilayer microchip system in which long-term stable horizontal free-standing and hydrogel-supported bilayers can be formed and demonstrate its prospects particularly for single-molecule fluorescence spectroscopy and high resolution fluorescence microscopy in probing the physicochemical properties like phase behavior of the bilayer-forming lipids, as well as in functional studies of membrane proteins.